Speaking of Culture - Weil, Nolan (Open textbook library., 2017)
“Speaking of Culture” is a collection of instructor-authored background readings intended to accompany other activities, discussions, experiences, projects, and readings for IELI 2470 – Cross-Cultural Perspectives, a course offered by faculty in the Intensive English Language Institute at Utah State University. Its main purpose is to define culture and other concepts often associated with it.